Comparative Analysis of Cube and Star Based Networks - Nasir, Faizan; Siddiqui, Jamshed (International Journal of Computer Sciences and Engineering, 2025)
Parallel computing is a variant of computation in which many calculations or execution of many processes are performed concurrently. Large and complex problems can be divided into smaller sub problems, which can be then solved at the same time. Network topology is the key factor of performance for any parallel computer. There are many proposed interconnection network topologies in order to achieve high performance. To trace out the better topology on the basis of standard parameter’s performance analysis, we have compared cube based networks and star based networks for the same parameters such as diameter, cost, average distance, message density. In this comparative study various aspects are discussed while designing an efficient multiprocessor interconnection network.